Stability and Robust Stabilization of 2-D Continuous Systems in Roesser Model Based on GKYP Lemma - Ismail Errachid; Abdelaziz Hmamed (International Journal of Power Electronics and Drive Systems (IJPEDS), 2017)
This paper is concerned with the stability and Robust stabilization problem for 2-D continuous systems in Roesser model, based on Generalized Kalman$-$Yakubovich$-$Popov lemma in combination with frequency-partitioning approach. Sufficient conditions of stability of the systems are formulated via linear matrix inequality technique. Finally, numerical examples are given to illustrate the effectiveness of the proposed method.